Determinan Nilai Perusahaan dengan Ukuran Perusahaan dan Leverage sebagai Pemoderasi pada Perusahaan Konstruksi - Muammar Muammar; Dwi Orbaningsih; Ahmad Ahmad (Program Studi Akuntansi, Universitas Kuningan, 2020)
This study aims to determine the determinants of firm value with firm size and leverage as moderating variables in construction companies. This research was conducted at a construction company. This is because the construction company is one of the biggest contributors to Gross Domestic Product (GDP) in Indonesia. The research method used is quantitative-comparative with the research sample are construction companies listed on the Stock Exchange with the 2014-2017 observation period determined through purposive sampling. There are 9 companies that meet the criteria. And there are 36 observations. The analytical method used is Multiple Regression Analysis and Moderation Regression Analysis (MRA). With the results of the study a) Disclosure of CSR does not affect the value of the company, b) The size of the company is not able to influence the disclosure of CSR with company value, c) Leverage can influence the disclosure of CSR with company value, d) Managerial ownership does not affect company value, e) Size companies cannot influence between Managerial Ownership and company Value and f) Leverage is not able to influence between Managerial Ownership and Corporate Value.Keywords : CSR Disclosure, Managerial Ownership, Company Size, Leverage, Company Value